Growth and productivity of tapioca (manihot utilissima) ii. stomatal functioning and yield - Williams, C.N. (Cambridge University Press, 1971)
The stomatal functioning of high, medium and low yielding clones of tapioca was examined to see whether yield could be associated with conductivity and/or resistance to moisture stress. A sensitive falling pressure porometer was used to measure stomatal conductivity to the viscous flow of air at small pressure differences. No marked differences were observed which could account for the large range in yields shown by the varieties, but stomatal functioning could be related to canopy type and to planting conditions. In general the conductivity values of all three varieties were very low compared to many other crop species, which suggests that increases in canopy efficiency and yield could be obtained in certain environments by an increase in leaf conductivity. © 1971, Cambridge University Press. All rights reserved.